EXALTATION OF LEGAL CULTURE IN SOCIETY - Suyunboyev Abbosbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the fact that this article approved the “roadmap” for the effective implementation of the concept of raising the legal culture in society in 2019 serves to ensure the implementation of the measures established in this regard.